A bibliometric analysis of the 100 most cited articles on early childhood caries. Issue 5 (20th April 2020) - Patil, Sneha S.; Sarode, Sachin C.; Sarode, Gargi S.; Gadbail, Amol R.; Gondivkar, Shailesh; Kontham, Ujwal R.; Alqahtani, Khaled M.
Abstract: Background: Bibliometric analysis aids to quantify the research prolificacy. The citation count acquired by a scientific article is one of the measures of its influence within a field. Aim: To employ bibliometrics to offer a quantitative‐qualitative analysis of publications on early childhood caries (ECC) published between 1950 and 2019. Design: Two researchers independently read all the titles and abstracts of articles retrieved from Scopus database on 16 October 2019. The articles were categorized according to citation and study characteristics. Collaboration network amongst authors, countries, and keywords were generated using VOSviewer software. Results: Amongst a total of 10 578 articles published on ECC, 100 most cited articles were sorted. The top‐cited articles appeared in 34 journals, with Community Dentistry and Oral Epidemiology journal (n = 18) contributing maximum number of articles. The papers originated from 25 countries, with the United States (n = 54) accounting for largest number. Amid the papers with high levels of evidence, 11 were systematic reviews and 8 were randomized clinical trials. The topic most commonly addressed was aetiology/associated factors (63%). Amongst a total of 990 keywords, 'dental caries' appeared 89 times. Conclusion: The findings of this paper will help researchers, academicians, and students for appropriate article referrals for evidence‐based clinical decision‐making.